PENDETEKSI GEMPA DENGAN METODE FM BERBASIS PERSONAL COMPUTER - Zaidir Jamal (Jurnal Informatika, 2011)
Generally, earthquake is measured with a seismometer, a device which is also known as seismograph  that works based on  detection of seismic wave in earth’s crust.  This research designs and implements an earthquake detection using frequency modulation method based on personal computer.  The research results a system and simulation. Simulation shows that in a normal condition the strength carrier is 2,5 % and before the earthquake occurred, the strength carrier is 55%. Frequency modulation method can be implemented  to detect earthquake by building some measurement stations at several   places.Keyword : earthquake, frequency modulation, seismograph